British general election Of 1959 - Butler, D.E. (London, 1960)
THE 1959 election, like its three predecessors, showed a swing to the right. The Conservative party, already comfortably in office, was returned again with a majority unmatched since the 1945 parliament. But, although the result was clear cut, the contest was not dull. In the manner of its conduct and the implications of its outcome, it was the most interesting of recent elections. It was carried on with an unprecedented air of self-consciousness. The commentaries during and after the campaign reached a new level of psephological sophistication. The discussions of marginal seats and of swing, the use of opinion polls, and the evaluations of canvass returns and of candidates' pulling power were all more in formed and realistic than in previous elections. If the press articles of 1955 and 1959 on how to interpret the returns on election night are compared, the scale of this advance becomes plain.
Keywords: Elections